2020
DOI: 10.1186/s12889-020-09036-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a group-based intervention program on physical activity and health-related outcomes in worksite settings

Abstract: Background: The benefits of physical activity (PA) have been well documented, and the worksite is a promising setting for PA promotion. The aims of this study were as follows: 1. To evaluate the effect of a group-based worksite intervention on PA and health-related outcomes by using pedometers. 2. To examine the associations between the change in vigorous physical activity (VPA)/moderate physical activity (MPA)/walking and health related outcomes. Methods: A total of 398 participants (221 in the intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…Of these 17 countries/territories, eight are classified as high‐income, six are upper middle‐income, and three are lower middle‐income countries/territories. In total, 52 studies were conducted in high‐income (65.0% 54,55,57–81,90–108,113–116,129,131 ), 23 in upper middle‐ (28.7% 82–84,86–89,109–112,117–124,128,132,133 ), and five in lower middle‐income countries/territories (6.3% 51,125–127,130 ). There were no studies from low‐income countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these 17 countries/territories, eight are classified as high‐income, six are upper middle‐income, and three are lower middle‐income countries/territories. In total, 52 studies were conducted in high‐income (65.0% 54,55,57–81,90–108,113–116,129,131 ), 23 in upper middle‐ (28.7% 82–84,86–89,109–112,117–124,128,132,133 ), and five in lower middle‐income countries/territories (6.3% 51,125–127,130 ). There were no studies from low‐income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Over half (43/80, 53.8% 51,55,57–60,62–66,68,71,72,74,80,83–85,87,88,91,92,94,99,106,108,111,112,117–119,122–126,129,132,133 ) of studies did not report a theoretical framework for intervention development. Of the 37 studies (46.3% 54,61,67,69,70,73,75–79,82,86,89,90,93,95–98,100–105,107,109,110,113–116,121,127,128,130,131 ) that did, social‐cognitive theory was most commonly reported (8/80, 10.0% 54,76,86,97,104,105,107,121 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Developing interventions in targeting these reasons and solving these barriers for non-urban villagers will be important step for increase the proportion of non-urban villagers in engaging in recreational physical activity. For example, Gu et al [ 41 ] found change in physical activity among office workers after the implementation of a worksite intervention programs at 17 worksites in the urban city of Shanghai with pedometers for 100 days. The goal of using and developing physical activity interventions are to promote recreational physical activity levels among both urban villagers and non-urban villagers.…”
Section: Discussionmentioning
confidence: 99%